PAPUA PEGUNUNGAN DALAM BAYANG-BAYANG INFLASI: TELAAH KRITIS ATAS FENOMENA DEPENDENSI DALAM BINGKAI EKONOMI POLITIK - K Belolon, Handrianus (KRITIS, 2025)
ABSTRACT Mountainous Papua faces significant economic challenges, including high inflation rates that hinder social development and community welfare. One of the primary factors behind this issue is economic dependency on central regions and developed countries for essential supplies, technology, and economic policies. This article examines the phenomenon of inflation in Mountainous Papua through a critical dependency theory approach, focusing on the asymmetric relationship between peripheral and central regions. Using a political economy framework, the article argues that sustained dependency contributes to economic instability and vulnerability to poverty. Therefore, a strategic plan is necessary to establish an inclusive economic ecosystem as a pathway out of the grip of inflation.